2015
DOI: 10.1007/s10681-015-1477-1
|View full text |Cite
|
Sign up to set email alerts
|

Association mapping of seed germination and seedling growth at three conditions in indica rice (Oryza sativa L.)

Abstract: Seed germination and seedling establishment are critical phases in rice. In this study, 276 indica accessions were used to investigate the genetic control of seed germination and seedling growth under normal, drought and salt conditions by using the trait of germination percentage, germination index and seedling survival percentage. The significant natural variation of seed germination and seedling growth was observed among accessions at three conditions. Correlation analysis showed that the significant and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 54 publications
(60 reference statements)
1
35
0
Order By: Relevance
“…Previous studies have shown that salinity tolerance is developmentally regulated and growth stage-specific in rice (Cheng et al, 2015). Therefore, the development of rice varieties with vigorous germination and seedling growth simultaneously under salinity stress is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that salinity tolerance is developmentally regulated and growth stage-specific in rice (Cheng et al, 2015). Therefore, the development of rice varieties with vigorous germination and seedling growth simultaneously under salinity stress is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Seed germination is a complex process that can be influenced by many factors, such as seed size, genotype, seed development, storage time and environment (Sun et al, 2007;Milošević et al, 2010). To date, numerous quantitative trait loci (QTLs) for seed germination have been reported in rice (Miura et al, 2002;Fujino et al, 2004;Jiang et al, 2006;Fujino et al, 2008;Wang et al, 2010;Li et al, 2013;Liu et al, 2014;Xie et al, 2014;Cheng et al, 2015;Hsu and Tung, 2015;Kretzschmar et al, 2015;Jiang et al, 2017;Wang et al, 2017;Jin et al, 2018). However, cloned genes related to the control of rice seed germination are still rare.…”
Section: Introductionmentioning
confidence: 99%
“…These include indica/indica (Cui et al 2002;Xie et al 2014) and japonica/japonica (Yang et al 2010;Abe et al 2012) crosses. More recently, association mapping strategies have been employed to detect seedling vigor QTL in natural populations of rice varieties (primarily indica) and landraces (Dang et al 2014;Cheng et al 2015;Wu et al 2015;Anandan et al 2016;Lu et al 2016).…”
Section: Introductionmentioning
confidence: 99%